Pengembangan Potensi Curug Leuwi Pamipiran Sebagai Objek Wisata Melalaui Sosialisasi Penguatan Kelembagaan Di Desa Tanjungsari Kabupaten Ciamis - Cantika Mutiara K; Ii Sujai; Repa Nurlaela; Resti Illa R; Siti Soleha (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2024)
Management Community-based natural resource management and conservation is an effective approach in maintaining environmental sustainability and improving the welfare of local communities. This research aims to analyze the natural resource management and conservation strategies implemented by the people of Tanjungsari Village, Sadananya District, Ciamis Regency. The research method used is a qualitative approach with data collection techniques through in-depth interviews, participatory observation, and documentation studies. The results showed that the Tanjungsari Village community has developed various local initiatives to preserve water sources, and manage tourist attractions in the village. The active participation of the community in conservation activities, support from the local government, and cooperation with non-governmental organizations are key factors in the success of this program. The study concludes that a community-based approach to natural resource management is not only able to preserve the environment, but also contributes to improving the economic and social welfare of local communities. In addition to management, socialization was held. The implementation of these socialization activities is proven to increase the understanding and skills of the community in managing tourism potential in a sustainable manner. In addition, support from the local government and active participation of the community are important factors in the development of curug lewi pamipiran as a leading tourist attraction in Ciamis Regency. This study concludes that institutional strengthening through socialization and training is an effective strategy to optimize regional tourism potential, improve community welfare, and encourage local economic development.